Comparative study of rabbit ear mange treatment and epizootic aspects in medicinal prevention - Donkó, Tamás (Acta Agraria Kaposváriensis, 1999)
Natural cases of ear mange in rabbits caused by Psoroptes cuniculi were examined by otoscope. The evaluation of the severity of symptoms was based on scores 0–10 (where 0 indicates asymptomatic and 10 the most serious ear mange in the whole ear). The medicines used for the treatments were ivermectin [Ivomec injection (MSD AgVet)], tetrametrin [Neostomosan (Sanofi PHYLAXIA)] and diazinon [Neocidol (NOVARTIS)]. Change in symptoms (i.e., efficacy) and the relationship between symptoms (infestations) in does and in their offspring, and also the efficacy of single and repeated treatment, were evaluated in the course of the experiment. Infestations in offspring 1, 3 and 5 months after the ivermectin injection treatment of does were also studied. The ivermectin injection proved to be the most efficient, and Neocidol was higher in efficacy than Neostomosan. The repeated treatments were more effective than the single ones. The degree of infestation of does proved to determine to a degree of 70% probability that occurring in their offspring (R2 = 0.74). As time passed after the ivermectin injection treatment of the does, symptoms in their offspring became increasingly serious. Cost analysis of the various treatments was also performed. Mainly based on the conclusions drawn from the experiment, and also on theoretical and practical consideration, the author recommends that does be treated by ivermectin injection in a programme (200 µg/bw kg) 4 x 2 times per year. Where necessary local treatment of offspring with Neocidol (diazinon) is recommended.